1988
DOI: 10.1161/01.hyp.12.2.108
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous digitalislike circulating substances in spontaneously hypertensive rats.

Abstract: SUMMARY Circulating digitalislike compounds have been proposed to be involved in some Na+ -dependent types of experimental hypertension and in human essential hypertension. The level of circulating Na + -K + pump inhibitor(s) was investigated in the spontaneously hypertensive rat of the Okamoto strain (SHR), its normotensive control, Wistar-Kyoto rat (WKY), and the regular Wistar rat using the following criteria: the ability of whole plasma to inhibit the total active Na + efflux from Wistar rat erythrocytes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 45 publications
2
3
0
1
Order By: Relevance
“…Moreover, the [3Hlouabain levels both in plasma and adrenals were significantly higher in SHR than in WKY from the age of 6 wk, just after the beginning of systolic BP elevation, onward. This observation is also partly compatible with the previous report (16) that the plasma of SHR showed higher inhibition of Na+ efflux from erythrocytes and of Na+,K+-ATPase as well as higher digoxin-like immunoreactivity than did the plasma of WKY. All these observations indicate that [3H]ouabain of dietary origin mimics the kinetics and pathophysiological roles of EDLF.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, the [3Hlouabain levels both in plasma and adrenals were significantly higher in SHR than in WKY from the age of 6 wk, just after the beginning of systolic BP elevation, onward. This observation is also partly compatible with the previous report (16) that the plasma of SHR showed higher inhibition of Na+ efflux from erythrocytes and of Na+,K+-ATPase as well as higher digoxin-like immunoreactivity than did the plasma of WKY. All these observations indicate that [3H]ouabain of dietary origin mimics the kinetics and pathophysiological roles of EDLF.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, reversephase HPLC showed that orally ingested [3H] ouabain was not metabolized and was present in the plasma and various organs, including the adrenal glands. These results are partly compatible with those of a previous pharmacokinetic study in which intravenously administered ouabain was not metabolized in the mammalian body (16).…”
Section: Discussionsupporting
confidence: 91%
“…Chronic increases in arterial pressure may result from primary defects in renal function 36 " 39 or increased plasma levels of circulating hormones or as yet unidentified circulating factors. 40 …”
Section: Primary Versus Secondary Role Of the Baroreceptor Reflex In mentioning
confidence: 99%
“…Several investigations have provided evidence for elevated levels of circulating sodium pump inhibitors in hypertensive subjects (Hamlyn & Manunta 1992) and experimental animals (Wauquier et al 1988;Doris 1994). This digitalis-like factor augments natriuresis, but it also depolarizes smooth muscle via Na π ,K π -ATPase inhibition, and increases calcium influx through voltage-dependent channels.…”
Section: Discussionmentioning
confidence: 99%
“…The altered function of Na π ,K π -ATPase may play a role in the pathogenesis of hypertension, and elevated levels of circulating sodium pump inhibitors have been found in hypertensive patients (Hamlyn & Manunta 1992) and experimental animals (Wauquier et al 1988;Doris 1994). This digitalis-like factor is a natriuretic agent, but it depolarizes arterial smooth muscle via Na π ,K π -ATPase inhibition, and thus elevates peripheral resistance (Zhu et al 1994).…”
mentioning
confidence: 99%